Comparative microbiome analysis of paired mucosal and fecal samples in Korean colorectal cancer patients - Kim, Younggwang; Kim, Min Ki; Lee, Sanghun (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is increasingly linked to gut microbiome dysbiosis. However, few studies have examined tumor-associated microbial dynamics in Korean CRC patients using both mucosal and fecal samples.MethodsWe analyzed paired fecal and mucosal samples from 30 Korean CRC patients aged 60–80 years before and after surgery. Microbial DNA was sequenced using 16S rRNA gene analysis. Diversity metrics, differential abundance testing (LEfSe), and pathway prediction (PICRUSt2) were performed. Diagnostic performance was evaluated with ROC curves, and associations with clinical parameters were assessed via regression models.ResultsBeta diversity revealed significant compositional differences between fecal and mucosal samples (p = 0.001), with mucosal samples showing higher enrichment of CRC-associated taxa. Fusobacterium, Prevotella 9, Parvimonas, and Holdemanella were significantly enriched in pre-surgical samples and declined after surgery (p < 0.01). Combined microbial markers yielded an AUC of 0.841 for distinguishing pre- from post-surgical status. Functional predictions indicated upregulation of amino acid metabolism and lipopolysaccharide (LPS) biosynthesis pathways in pre-surgical samples. Notably, Fusobacterium abundance correlated with TNM stage (p = 0.028), and Prevotella 9 abundance decreased with age (p = 0.006).ConclusionThis study highlights distinct microbial and functional signatures in CRC, particularly from mucosal samples, which offer deeper insights into tumor-microbiota interactions. The identified microbial markers and enriched pathways may contribute to immune modulation and tumor progression. These findings support the potential for microbiome-based diagnostic and therapeutic strategies tailored to Korean CRC patients and underscore the importance of dual-sample analysis in microbiome research.